Financial Technology Adoption Behavior in West Kalimantan: Examining the Role of Financial Literacy - Ayub, Jhon Stone Esau; Wendy (Yayasan Sinergi Kawula Muda, 2025)
This study examines how financial literacy influences financial technology adoption among Generation Z and Millennials in West Kalimantan. Despite the fintech industry's rapid growth revolutionizing financial services, challenges persist in young generations' understanding of financial products. The research addresses the primary issue of low financial literacy levels in West Kalimantan compared to national averages, which hinders effective financial decision-making. Using a quantitative survey approach, the study collected data from 233 Generation Z and Millennial respondents in West Kalimantan. Questionnaires gathered demographic information and indicators related to financial literacy and behavioral intention to adopt fintech. Data analysis employed Structural Equation Modeling with a Partial Least Squares approach using SmartPLS 3 software. Results reveal that financial literacy as a moderating variable shows a positive trend but does not significantly affect behavioral intention to adopt fintech. The findings suggest that Generation Z and Millennials in West Kalimantan adopt fintech primarily due to perceived benefits, ease of use, work-related utility, and self-control rather than financial knowledge. The study emphasizes the importance of enhancing financial literacy for optimal fintech service utilization among young generations. Higher financial literacy levels correlate with increased behavioral intention to adopt fintech services. This research highlights the need for more effective financial education programs targeting young generations to promote wiser fintech usage. The key conclusion underscores that improving financial literacy is essential for broader and more sustainable fintech adoption in the region